Transmitter for 5G systems - Marques, Rúben Pereira (2019)
The current 4G systems are based on the OFDM modulation which, while providing great exibility and intricacy to the multipath propagation inherent in wireless systems, it has great variations in their temporal envelope which causes high PAPR and, consequently, obstacles in the PAs performance. In this sense, the emergence of 5G systems has given rise high hopes of reducing the above mentioned problems of 4G systems, allowing more eficient data transmission. In the simulation of wireless communication system there are two simulation domains that must be taken into account: the system analysis that allows the study of diferent modulations and the circuit analysis that, in turn, allows the study of nonlinear circuits, as is the case of PAs present in these systems. In this way, it becomes important to unite these two domains allowing the existence of a unifying simulation tool, which has been called the simulation platform. With this platform it is possible, besides joining two domains hitherto analyzed separately, not only to study the behaviour of a 5G system but also any other system due to its adaptability. Thus, the system analysis is performed with the help of MATLAB software, in which three types of digital modulation (QPSK, 16-QAM and 64-QAM modulation) will be studied along with OFDM modulation. For the circuit analysis it was used the ADS circuit simulation software, which will analyze the behavior of two types of PAs (a Class B and a Doherty). As a way of testing its functioning, the platform simulations were performed for three diferent con gurations: SISO, SISO in which the PA model was replaced by a polynomial approximation, and Alamouti 2x1 (particular case of the MISO con guration). Finally, the tests of functioning of the simulation platform are nalized with the comparison of the simulations using the BER